PER-SATU-TUBUH-AN SEBAGAI SIMBOL POLA RELASI LAKI-LAKI DAN PEREMPUAN (Sebuah Konsep Kesetaraan Gender dalam Al-Quran) - Widodo, Aris (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2015)
Since the last decades of twentieth century, gender discourse has become a hot issue among Indonesian Muslim intellectuals. This phenomenon cannot be detached from international socio-intellectual constellation. In 1970?s, gender issue became a significant discourse in England. From then on, the discourse spread to many countries, including Indonesia. The result is that many Western perspectives on the issue inspired Muslim intellectuals. One of the influences is the using of terms such as ?domination?, ?sub-ordination?, and ?equality?. This article tries to describe how the perceptions of domination, sub-ordination, and equality emerged in Western culture. This is followed by examples of Muslim intellectuals? thoughts inspired by the perspective. Finally, the writer will provide a concept of relationship of man and woman based on an understanding on Qur?anic verses. It is argued that man and woman are equal in terms of quality. Yet, man and woman may differ if quantity is concerned.